10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Increased posterior tibial slope (PTS) has been associated with higher revision rates after anterior cruciate ligament reconstruction (ACLR). Whether the addition of lateral extra-articular tenodesis (LET) mitigates the risk associated with increased PTS is unclear. PURPOSE: To determine the prevalence of increased PTS (≥12°) in a young high-risk primary ACLR population and evaluate whether LET is associated with lower revision rates in patients with increased PTS. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: This study included patients aged ≤25 years undergoing primary ACLR across 3 high-volume centers with ≥2 years between surgery and data collection. PTS was measured on lateral radiographs for medial and lateral plateaus. Primary analyses consisted of 4 prespecified multivariable logistic regression models with different PTS operationalizations as continuous predictors per 1° increase (medial PTS, lateral PTS, the maximum [PTSmax], and the lateral-medial difference), adjusted for patient and surgical covariates including graft type, with surgical center as a fixed effect. Secondary analyses used PTS dichotomized at 12°; revision rates were compared between isolated ACLR and ACLR with LET, with the treatment effect quantified as absolute risk reduction and number needed to treat. RESULTS: A total of 780 patients were included; 84 (10.8%) underwent revision ACLR. Increased PTS (≥12°) was present in 28.2% of patients and more common in those requiring revision (38.6% vs 27.0%; P = .03). In patients with PTSmax ≥12°, revision occurred in 21.0% without LET and 9.2% with LET (absolute risk reduction, 11.8% [95% CI, 2.3%-21.3%]; number needed to treat, 9); in patients with PTSmax <12°, revision occurred in 13.2% without LET and 5.4% with LET (absolute risk reduction, 7.8% [95% CI, 3.0%-12.6%]; number needed to treat, 13). In the 4 prespecified multivariable models with PTS as a continuous predictor, LET was independently associated with substantially lower odds of revision ACLR (odds ratio [OR], 0.37; 95% CI, 0.22-0.62; P < .001). Lateral PTS (OR, 1.09 per 1° increase; 95% CI, 1.00-1.18; P = .04) and PTSmax (OR, 1.09; 95% CI, 1.00-1.19; P = .04) were independently associated with revision ACLR. The lateral-medial PTS difference was not associated with revision ACLR. CONCLUSION: In a young high-risk primary ACLR population, increased PTS was present in nearly 30% of patients. LET was associated with a lower risk of revision irrespective of PTS, while increased PTS was independently associated with revision ACLR.